Tracking SARS-CoV-2 in urban wastewater samples during the first wave of COVID-19 epidemic in Lombardy (Italy). (March 2022) - Pellegrinelli, L.; Schiarea, S.; Primache, V.; Galli, C.; Bubba, L.; Mancinelli, F.; Cereda, D.; Ammoni, E.; Pariani, E.; Castiglioni, S.; Zuccato, E.; Binda, S.
Abstract : Purpose: The value of SARS-CoV-2 monitoring in urban wastewater samples (WWS) for surveillance of virus spread at a population-wide level has been largely demonstrated. Aim of this study was to optimize an analytical workflow to detect SARS-CoV-2 RNA in WWS and to monitor SARS-CoV-2 spread during the first wave of COVID-19 epidemic (March–June 2020) in Lombardy, northern Italy. Methods & Materials: The workflow consisted in WWS concentration by using PEG-8000 precipitation, a modified RNA extraction (QIAamp MinElute Virus Spin Kit; QIAGEN) and a one-step real-time RT-PCR detecting two portions of the N gene of SARS-CoV-2. Composite 24-hour WWS were collected once a week at the inlet of 8 wastewater treatment plants (WWTPs) with an overall catchment of 2, 276, 000 inhabitants, located in representative COVID-19 hotspots in Lombardy, from the end of March to mid-June 2020. 107 WWS were obtained and analysed. SARS-CoV-2 RNA copies/L/WWS were multiplied by the flow rate of each WWTP (m3/day) and the obtained load (copies/day/1, 000 people) was normalized to the number of inhabitants served by WWTPs. Results: The optimized workflow allowed to identify 1E+3 copies/mL of SARS-CoV-2 in concentrated WWS with a turnaround time of 8 hours. Overall, the presence of SARS-CoV-2 RNA was identified in 65/107 WWS (61%). The highest rate of positive WWS (78.7%; 26/33) was identified in the Bergamo province, that was the epicentre during the first wave of COVID-19 epidemic (March-June 2020) in Lombardy. The highest amount of SARS-CoV-2 RNA was identified in late March/early April, when the overall viral load reflecting the number of individuals shedding the virus ranged from 9.3E+10 copies/day/1, 000 people to 8.2E+8 copies/day/1, 000 people. Since the end of May, WWS tested negative to SARS-CoV-2 detection. Conclusion: According to the epidemiological features of the first wave of SARS-CoV-2 epidemic in Lombardy, the highest amount of SARS-CoV-2 RNA was detected in WWS collected in the areas most affected by COVID-19 (i.e. Bergamo province). This optimized workflow of WWS surveillance can help assessing the real number of individuals – both symptomatic and asymptomatic – able to spread the virus and appraising the effect of preventive measures.